Pengaruh Penggunaan Aplikasi Leads Terhadap Peningkatan Kualitas Pembelajaran Mahasiswa Kedokteran UPN Veteran Jakarta - Nathanael, Garcia Krisnando (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Technological advances not only lie in the speed factor to get information but also multimedia facilities that can make learning more interesting to encourage students to learn optimally both in independent learning and in classroom learning. This study aims to determine the level of learning quality of UPN